Local tuberculosis in children of the tender age - L. V. Poddubnaya; G. F. Dubakova; A. N. Kurlaeva; T. I. Gurdina; K. M. Trapeznikova; E. P. Shilova (Туберкулез и болезни лёгких)
The purpose is to study clinical and X-ray manifestations of local tuberculosis in children of the tender age and to detect risk factors promoting the development of the disease and complicating it, thus the analysis included 82 cases of children cases under 3 years old who had been treated in Children TB Hospital in 2013-2015. Tuberculosis of chest lymph nodes was diagnosed in 68.3%of them, and every fifth child had primary tuberculosis complex. Every other child was suffering from the complicated course of local tuberculosis (n = 42). The following forms were registered: bronchial pulmonary lesions (n = 27), lymphogenic progression (n = 13), including development of disseminated tuberculosis and meningitis. Positive results of sputum tests were observed in 14 (17.1%) children, of them 50% had multiple drug resistance. 10% of children suffering from tuberculosis manifested anergy. The predictors of such course of the disease included the absence of BCG vaccination and super infection with Mycobacterium tuberculosis.